1991
DOI: 10.1002/cjce.5450690413
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of the pyrolysis of biomass particles. Studies on kinetics, thermal and heat transfer effects

Abstract: The present work provides a rationally‐based model to describe the pyrolysis of a single solid particle of biomass. As the phenomena governing the pyrolysis of a biomass particle are both chemical (primary and secondary reactions) and physical (mainly heat transfer phenomena), the presented model couples heat transport with chemical kinetics. The thermal properties included in the model are considered to be linear functions of temperature and conversion, and have been estimated from literature data or by fitti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
181
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(191 citation statements)
references
References 16 publications
8
181
0
2
Order By: Relevance
“…Specific heat as a function of multiple variables may be incorporated into the energy balance equation in order to predict the temperature profiles with great accuracy (Koufopanos et al, 1991). Similar equations were obtained for lignocellulosic waste materials, such as banana flowerstalk (Villa-Vélez et al, 2015a) and woods (Koufopanos et al, 1991). In general terms, the three models showed good and simple descriptions of the experimental data as functions of all parameters studied (R 2 adj > 0.967).…”
Section: Specific Heat and Mathematical Modelingmentioning
confidence: 71%
See 1 more Smart Citation
“…Specific heat as a function of multiple variables may be incorporated into the energy balance equation in order to predict the temperature profiles with great accuracy (Koufopanos et al, 1991). Similar equations were obtained for lignocellulosic waste materials, such as banana flowerstalk (Villa-Vélez et al, 2015a) and woods (Koufopanos et al, 1991). In general terms, the three models showed good and simple descriptions of the experimental data as functions of all parameters studied (R 2 adj > 0.967).…”
Section: Specific Heat and Mathematical Modelingmentioning
confidence: 71%
“…Higher values of c p were encountered for less concentrated suspensions since dry biomass has a lower specific heat than water (Collazo et al, 2012). Specific heat as a function of multiple variables may be incorporated into the energy balance equation in order to predict the temperature profiles with great accuracy (Koufopanos et al, 1991). Similar equations were obtained for lignocellulosic waste materials, such as banana flowerstalk (Villa-Vélez et al, 2015a) and woods (Koufopanos et al, 1991).…”
Section: Specific Heat and Mathematical Modelingmentioning
confidence: 95%
“…Temperature-dependent property variation was also studied by Matsumoto et al (1969), Kung (1972), Maa and Bailie (1973), Kansa et al (1977), Chan et al 1985). Multi-step reaction schemes have been presented by Tinney (1965), Kung (1972), Chan et al (1985) and Koufopanos et al (1991). The heat of reaction of pyrolysis have been modelled by Lee et al (1976), while the effect of anisotropy of the pyrolysing medium has been considered by Kansa et al (1977).…”
Section: Introductionmentioning
confidence: 99%
“…Villermaux et al (1986) presented a Volatilization Thermal Penetration model (VTP) for any kind of solid reaction where volatilization is controlled by heat conduction from the outer surface. On the modeling of pyrolysis of biomass particle, particularly on the studies of the kinetic, thermal and heat transfer effects, Koufopanos et al (1991) assumed the pyrolysis process to be primary and secondary kinetic reactions. Di Blasi (1993) analysed the effects of convection and secondary reactions within porous solid fuels undergoing pyrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…This model gave satisfaction only for wood particles whose diameters are lower than 20mm. Koufopanos et al [4] defined a model in which they coupled conduction heat transfer with chemical kinetics. They concluded that the reactions heat can be represented by endothermic or exothermic values according to the conversion rate.…”
Section: Introductionmentioning
confidence: 99%